Don DeLillo's cinematic imaginary: from A(mericana) to Z(ero K). Issue 10 (3rd October 2021) - Sheehan, Paul
ABSTRACT: In his fictional works and in interviews, Don DeLillo has always been open and forthcoming about what the cinema has meant to him, as a writer. This article plots the development of a 'cinematic imaginary' in DeLillo's works, by focusing on his ability to devise various kinds of uncanny, para-cinematic artefacts. Three novels in particular – Americana, Running Dog and Underworld – are based around elusive, enigmatic films-in-the-making, in which (filmic) genre asserts itself and the influence of Jean-Luc Godard continues to be felt. The discussion concludes on an elegiac note, as DeLillo moves away from the cinematic towards a different kind of imaginary in his late work.